The effect of nutrient dose and selected insecticides against corn earworm (Helicoverpa zea) in sweet corn / Muhamad Haika Jafri - Jafri, Muhamad Haika (Faculty of Plantation and Agrotechnology, 2018)
Sweet corn (Zea mays var. saccharata) is family of Gramineae. There are many varieties of sweet corn available in the market and under categorized of the cash crop plants. In this study, the selected varieties (King Corn F1 316®) has high sugar content. Corn earworm (Helicoverpa zea) is the most common of the sweet corn insects-pest and also major issue pest that feeds on kernel at the tip of the sweet corn ear. The damage caused by corn earworm may cause physical damage to the fruits and the sweet corn to be unmarketable and down grade the quality of sweet corn’s fruits. The study was aimed to determine the effects of nutrient doses and selected insecticides towards the Helicoverpa zea abundance and plant growth performances. Different variation of nutrient dosage were applied to sweet corn plants labelled as N1 (10gm), N2 (20gm) and N3 (60gm). Different nutrient levels were applied to evaluate the effects of different nutrient dosages towards Helicoverpa zea population on sweet corn. Subsequently, the sweet corn plants were also treated with chemicals to evaluate the efficacy of different types of chemical usage such as C1=Cypermethrin, C2=Malathion, C3=Soursop and C4=Control for controlling the Helicoverpa zea. The study measured the plant growth performances in relation to pest abundance in the field. The results revealed that N3 (60gm) of nutrient dose was recorded to be the highest Helicoverpa zea abundance followed by N2 (20gm) and N1 (10gm). For controlling aspect, Cypermethrin was the most effective against Helicoverpa zea abundance in sweet corn. Cypermethrin gave the highest reduction of corn earworm followed by Malathion, soursop and control. Overall, the highest amount of nutrient level can influenced the presence of Helicoverpa zea population, therefore, optimum amount of nutrient should be considered in planting the sweet corn for the whole planting period and the best selected chemical was Cypermethrin.